2018
DOI: 10.5430/cns.v6n4p53
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate final year nursing students’ attitudes toward caring for dying patients: Bahrain’s experience

Abstract: Background: Nursing students are frequently exposed to dying patients during their clinical placement. Research studies that examined nursing students’ attitudes toward caring for dying patients were limited in the Gulf Region, including Bahrain.Objective: The purpose of this study is to examine the attitudes of fourth-year baccalaureate nursing students regarding caring for dying patients.Methods: A descriptive cross-sectional design was utilized to recruit a convenience sample of fifty-four nursing students.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(44 reference statements)
1
5
0
1
Order By: Relevance
“…In the same assertion, nurses’ attitudes toward EOL care correlate with the years of experience; nurses with more experience developed a more favourable attitude toward death and dying. This affirms the findings from previous studies; [ 12 , 26 , 27 ] one possible explanation for this finding is that nurses with more experience might have cumulative skills and wider experiences in caring for dying patients while advancing in their careers. Novice nurses might need more time to cope with caring for dying patients.…”
Section: Discussionsupporting
confidence: 91%
“…In the same assertion, nurses’ attitudes toward EOL care correlate with the years of experience; nurses with more experience developed a more favourable attitude toward death and dying. This affirms the findings from previous studies; [ 12 , 26 , 27 ] one possible explanation for this finding is that nurses with more experience might have cumulative skills and wider experiences in caring for dying patients while advancing in their careers. Novice nurses might need more time to cope with caring for dying patients.…”
Section: Discussionsupporting
confidence: 91%
“…Nearly half of the students in both groups reported that they have worked with a terminal period patient and his family, also students in IG group had less difficulty talking with the patient about death than CG. In one study, nearly all of the nursing students reported having previous experience in dealing with terminally ill people, and they also stated they had neutral attitudes toward caring for dying patients (Yaqoob et al, 2018). In another study, last year nursing students developed positive attitudes toward dying in the field of palliative care education (Grubb & Arthur, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They also developed a great deal of knowledge and skills and they might have more experiences and opinions about the DNR than the other students. Also, several previous studies about end of Life Care and DNR recruited students in their final year (Bailey & Hewison, 2014;Jafari et al, 2015;Yaqoob et al, 2018). Participants (n = 213) were divided into interventional group (IG) (n = 106) and control group (CG) (n = 107) according to selection of elective course of palliative care by voluntarily.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses also seldom discussed with patients and family about the feelings because of the lack of privacy in ED (Decker et al, 2015). Barriers and obstacles in EOLC can affect the ability of nurses to communicate with patients and families regarding EOLC (Gurung & Timalsina, 2018) According to Yaqoob et al (2018), there was a relationship between gender and the attitude of nursing students towards EOLC. Other studies also revealed that women are considered to have a more positive attitude towards caring for dying patients than men (Lancaster et al, 2017).…”
Section: Discussionmentioning
confidence: 99%